PELATIHAN MICROSOFT OFFICE DALAM UPAYA PENGUATAN KOMPETENSI GURU SEKOLAH DASAR - I.M.S. Putra; D.P. Githa; I.P.A. Dharmaadi; I.M.S. Raharja; A.A.N.H. Susila; D.M.S. Arsa; N.P. Sutramiani; D.P.S. Putri; N.W.E.R. Dewi (Buletin Udayana Mengabdi, 2023)
Today's rapid development in the world of information technology causes almost all human work to become lighter and more effortless. One of them is the teacher's duties in teaching and giving grades. Applications already available on laptops or computers, such as Microsoft Office, can create more interactive teaching materials, create financial reports, or manage grades. However, most teachers who are familiar with laptops or computers can only operate the simple functions available in these applications, so the work that can be done is still limited. This service is carried out through training methods with material on using Microsoft Office applications (Word, Excel, PowerPoint) for teachers. The school being targeted is SD Negeri 7 Kesiman, whose environment is already fluent in technology but whose human resources are still limited in operating computers. The training material in the form of a Microsoft Office training module compiled by the service society team is used as a learning medium for teachers at SD Negeri 7 Kesiman. Evaluation of training activities used methods in the form of pre-test and post-test, in which the results showed that the ability of teachers at SD Negeri 7 Kesiman to understand the material had increased from before. These results also illustrate that the modules are arranged to make it easy to learn and conform to the needs of the features that the teacher often uses. Keywords : Competency, computer, information technology, Microsoft Office, teacher.